Challenges in Implementing Indonesia's Halal Product Assurance Law: An Analysis of Legal Uncertainty, Supervisory Systems, and Legal Culture - Nurhasanah, Nurhasanah; Al Haddad, Umar; Daud, Mohd Zaidi; Ariny, Bintan Dzumirroh; Laksmi, Lucy (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The presence of the government, which guarantees the availability of halal products and services through the JPH, Law has not provided legal certainty for Muslims to consume halal goods and services because they are still found circulating in the market without certification. This research aims to explore the complexity of problems in implementing JPH. The method used is qualitative with a normative and empirical approach. The analysis was carried out using Lawrence Friedman's legal system theory, which is relevant to Soerjono Soekanto's legal effectiveness theory, Robert W Mockler's legal supervision theory, and Philippe Nonet and Philip Selznick's responsive theory. This research concludes: first, legal uncertainty is caused by regulatory uncertainty due to rapid regulatory changes without good coordination between stakeholders. Second, a monitoring system that has not been integrated causes technical problems to be resolved slowly. Third, legal culture, such as literacy, knowledge, and legal awareness of the community and business actors, is inadequate. This research contributes as evaluation material in the implementation of JPH because it is comprehensive by using several legal theories as a guide for problem analysis. This evaluation material will have implications for improving the Authority's performance in the future.